Circular RNA hsa_circ_0076906 competes with OGN for miR-1305 biding site to alleviate the progression of osteoporosis. (May 2020) - Wen, Jian; Guan, Zhiping; Yu, Binsheng; Guo, Jing; Shi, Yan; Hu, Lisheng
Abstract: Osteoporosis is a skeletal disorder, the pathogenic factors of which include the decreased ability of osteogenesis and enhanced osteolysis. Human-derived mesenchymal stem cells (hMSCs) possess the differential capacity to osteoblasts and chondrocytes, so the application of hMSCs in bone tissue is promising to be effective. A group of RNAs which lack of 5′ and 3′ends called circular RNAs (circRNAs) were discovered. In this study, we described a previously found circular RNA, circ_0076906, to bind miR-1305 and regulate its target gene, Osteoglycin (OGN), thus regulate osteogenic differentiation of hMSCs and alleviate the progression of osteoporosis. Osteogenic differentiation induced in hMSCs; qRT-PCR and western blot to examine the expressions of mRNAs and proteins; Alkaline phosphatase activity and Alizarin red staining to examine bone formation; luciferase report experiments to detect the interaction between molecules; and the nuclear/cytoplasm separation of cells. 1. Circ_0076906 was induced in osteogenic differentiation; 2. Circ_0076906 silencing inhibited osteogenesis-related genes in hMSCs; 3. Circ_0076906 acted as a sponge for miR-1305; 4. MiR-1305 regulated OGN expression; 5. Circ_0076906 induced-osteogenic differentiation depended on miR-1305/ OGN pathway. Circ_0076906 relieved osteoporosis and promoted osteogenic differentiation through the miR-1305/ OGN pathway.